The Effect of Black Garlic (Allium sativum Linn) on Cardiac and Aortic Histopathology in Experimental Studies in Obesity Rats - Andreas Arie Setiawan; Fairuz Azmila Purnomo; Vega Karlowee; Noor Wijayahadi (Journal of Biomedicine and Translational Research, 2021)
ABSTRACTBackground: Obesity is a disorder or disease characterized by the accumulation of excess fat in the body due to an imbalance in energy intake that is used for a long time. Accumulation of fat can reduce adiponectin, causing cardiac hypertrophy, endothelial vasodilation, and other cardiovascular diseases. Black garlic have high antioxidants in the form of S-Allylcysteine(SAC) which functions to increase adiponectin. Objective: To determine the effect of Black garlic on the histopathological picture of the heart and aorta of obese rats. Methods: This study was an experimental study with a randomized post-test only design with control group design with 5 groups of male white rats Sprague Dawley (Rattus novergicus) fed High Fat Fructose. Diet (HFFD) enriched with 1.25% cholesterol and 0.5% cholic acid for 8 weeks and was given black garlic intervention at doses of 450 mg / 200BW, 900mg / 200BW and 1350mg200 / BW for 4 weeks. Results: Giving black garlic significantly reduced body weight of rats (p = 0.001), and the results did not significantly reduce heart weight (p = 0.147), aortic weight (p = 0.061), histopathological changes in heart wall thickness (p = 0.423) and aortic wall thickness (p = 0.802). The effective doses of black garlic in this study were 450 mg / 200 grams BW, 900 mg / 200 grams rat BW and 1350 mg / 200 grams BW of rats. The optimal dose is 900 mg / 200 grams BW. Conclusion: Black garlic gave a significant reduction in body weight of rats and no significant reduction in heart weight, aortic weight, cardiac and aortic histopathological features.